Research Progress of Bathing in Pediatric Atopic Dermatitis - LIU Zhengqiang; YU Hong (Xiehe Yixue Zazhi, 2023)
Atopic dermatitis (AD) is a common chronic inflammatory skin disease characterized by recurrent eczematous lesions with dry skin and refractory pruritus. The pathogenesis of AD is complex and one of the reasons may be related to the skin microbial environment. Multiple studies have found that bathing may be associated to skin barrier function and different bathing method may affect the severity of AD. This paper focuses on the bathing method of children with AD as well as the cleansers, and reviews relevant guidelines and evidence-based medicine.